Advanced aqueous sodium-ion capacitors based on Ni0.25Mn0.75O nanoparticles encapsulated in electrospinning carbon nanofibers. Issue 42 (11th October 2022) - Gao, Mingyu; Song, Xinjian; Tan, Jianfeng
Abstract : Manganese oxides are promising cathode material candidates with appropriate positive potential windows for low-cost and safe aqueous sodium-ion capacitors (ASICs). Abstract : Manganese oxides are promising cathode material candidates with appropriate positive potential windows for low-cost and safe aqueous sodium-ion capacitors (ASICs). However, their low electrical conductivity issue and the lack of advanced binder-free manganese oxide-based electrodes severely restrict their practical capacitance and application in flexible ASICs. Here, Ni0.25 Mn0.75 O (NMO) nanoparticles uniformly encapsulated in carbon nanofiber films with excellent flexibility are fabricated by electrospinning and subsequent carbonization. The uniformly amorphous carbon layer enhances the conductivity, avoids dissolution and alleviates the volume or stress change of NMO during ion intercalation or mechanical deformation. More importantly, compared with the flexible electrodes prepared by traditional methods, electrospinning materials can be directly used as binder-free electrodes, which can effectively simplify the process and improve the energy density. Finally, a 2.4 V flexible quasi-solid-state ASIC device is integrated, which exhibits a high energy density of 5.95 mWh cm −3, a high power density of 670 mW cm −3 and an outstanding stability of 1000 cycles. This work offers an effective materials engineering strategy for high-performance binder-free NMO-based cathodes and advanced flexible ASICs.